The homeopathic treatment of concentration issues associated with attention deficit hyperactivity disorder in adults: a case report. - Lee, Lauren (Australian Journal of Herbal & Naturopathic Medicine, 2024)
Attention Deficit Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder characterised by inattention and/or hyperactivity-impulsivity, lasting for at least six months, and resulting in impaired social, academic, and occupational functioning. This case report concerns a 30-year-old female with ADHD-related concentration issues. The Boenninghausen Generalities Method and polarity analysis were used to categorise symptoms, followed by differentiation of medicines to determine the most indicated remedy, Phosphorus 200C.